Undernutrition, poor feeding practices, and low coverage of key nutrition interventions - Lutter, Chessa K.; Daelmans, Bernadette M. E. G.; de Onis, Mercedes; Kothari, Monika; Ruel, Marie T.; Arimond, Mary; Deitchler, Megan; Dewey, Kathryn G.; Blössner, Monika; Borghi, Elaine (American Academy of Pediatrics, 2011)
To estimate the global burden of malnutrition and highlight data on child feeding practices and coverage of key nutrition interventions.Linear mixed-effects modeling was used to estimate prevalence rates and numbers of underweight and stunted children according to United Nations region from 1990 to 2010 by using surveys from 147 countries. Indicators of infant and young child feeding practices and intervention coverage were calculated from Demographic and Health Survey data from 46 developing countries between 2002 and 2008.In 2010, globally, an estimated 27% (171 million) of children younger than 5 years were stunted and 16% (104 million) were underweight. Africa and Asia have more severe burdens of undernutrition, but the problem persists in some Latin American countries. Few children in the developing world benefit from optimal breastfeeding and complementary feeding practices. Fewer than half of infants were put to the breast within 1 hour of birth, and 36% of infants younger than 6 months were exclusively breastfed. Fewer than one-third of 6- to 23-month-old children met the minimum criteria for dietary diversity, and only ∼50% received the minimum number of meals. Although effective health-sector–based interventions for tackling childhood undernutrition are known, intervention-coverage data are available for only a small proportion of them and reveal mostly low coverage.Undernutrition continues to be high and progress toward reaching Millennium Development Goal 1 has been slow. Previously unrecognized extremely poor breastfeeding and complementary feeding practices and lack of comprehensive data on intervention coverage require urgent action to improve child nutrition.